#### Answer

See the picture below.

#### Work Step by Step

The parent function is $f(x)=(\frac{1}{3})^x$ (with red) the given function is $g(x)=(\frac{1}{3})^{-x}$ (with blue).
The parent function can be graphed by calculating a few coordinates and connecting them with a smooth curve:
$f(-2)=(\frac{1}{3})^{-2}=9$
$f(-1)=(\frac{1}{3})^{-1}=3$
$f(0)=(\frac{1}{3})^0=1$
$f(1)=(\frac{1}{3})^1=\frac{1}{3}$
$f(2)=(\frac{1}{3})^2=\frac{1}{9}$
For every corresponding x-value the following equation is true: $f(x)=g(-x)$
This means that the graph is reflected across the y-axis.
Because when f(x)=g(x), the g(x) function acts like the f(x).
For example if $f(-1)=3$ in the original $f(x)$, this will be equal to $g(1)=f(-1)=3$. $Here, f(-1)=g(1)$ also, $f(-2)=g(2)$
We can see that here, each point in the parent function was reflected across the y-axis.